A Modified Technique for Reliable Image Encryption Method using Merkle-Hellman Cryptosystem and Rsa Algorithm. (4th May 2015) - Lokeshwari, G.; Susarla, Sreevidya; Kumar, S. Udaya
Abstract: The great advances in digital data communication have led to high desire for a secured and reliable transmission. Advances in satellite communication like packet radio technology and the development of high speed LAN's have created demand for secured applications. Security measures are needed to protect data during transmission. Previous work has characterized reliable cryptosystem for applications like interactive communication, multimedia and data transfer. In this paper, a modified technique for reliable image encryption method using Merkle-Hellman cryptosystem and RSA algorithm is being proposed. By performing block rotation based upon the certain angles achieves better diffusion, which further enhances the security of cipher.